Extensive Forestry and Intensive Farming-slogan of the Day - Malik, O. P. (Indian Forester, 1973)
India is an agricultural country. Half of the country's area is under agricultural crops. Forests occupy only 23.1% of the land area while National Forest Policy envisages for prosperity of agricultural economy to bring at least one third area under forests. Forests are being ruthlessly felled and area brought under plough. The necessity of the day is to increase yield of agricultural crops per unit area and put more areas under forests for safeguard of agricultural. fields. The paper deals in brief that the production potential of the land under agriculture at present is more than three times the present yield while the area under forests is only two third of the required one. We must practise intensive forming and extensive forestry.